Dynamic Dual-Level Overcurrent Protection Scheme for Distributed Energy Resource Networks Using Digital Twins Technology - Feras Alasali; Naser El-Naily; Haytham Y. Mustafa; Hassen Loukil; Saad M. Saad; Abdelaziz Salah Saidi; William Holderbaum (International Transactions on Electrical Energy Systems)
The integration of distributed generators (DGs), particularly renewable energy sources, into conventional distribution networks (DNs) presents significant protection challenges. This study introduces a novel digital twins-based overcurrent relay (OCR) protection scheme with dynamic dual-level characteristic curves for microgrids. By utilizing advanced technologies such as digital-twin technology and hardware-in-the-loop (HIL) testing, the proposed scheme enhances fault management and relay coordination. Key contributions of this work include the integration of advanced technologies and dynamic OCR settings, using digital-twin technology and HIL testing to provide real-time insights and robust validation under practical conditions. Additionally, the research thoroughly examines protection strategies for both grid-connected and islanded modes, ensuring reliable operation during faults or grid failures. The study’s findings show substantial improvements over traditional OCR methods. The traditional OCR recorded a total tripping time of 14.87 s, while the dual-level OCR reduced it to 8.97 s. The results highlight the proposed scheme’s enhanced sensitivity, faster fault isolation capability, and overall superior performance, providing a robust and reliable protection scheme for modern power distribution systems. Further testing results for the digital-twin OCR, comparing both the digital simulation twin relay and the physical twin relay for the traditional single-level OCR scheme and the proposed dual-level scheme, provide valuable insights into the performance and reliability of these protection strategies. The close alignment between the simulation and physical results highlights the robustness and precision of the dual-level scheme.